2011
DOI: 10.1253/circj.cj-11-0103
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Endovascular Treatment of Critical Limb Ischemia

Abstract: Critical limb ischemia (CLI) represents the most severe clinical manifestation of peripheral arterial disease. In the absence of timely revascularization, CLI carries high risk of mortality and amputation. Over the past decade, endovascular revascularization has rapidly become the preferred primary treatment strategy for CLI, especially for the treatment of below-the-knee disease. Advances in percutaneous devices and techniques have expanded the spectrum of patients with CLI who are deemed candidates for revas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 50 publications
0
12
0
1
Order By: Relevance
“…20 Although there were several reports that suggested that this was advantageous for compromised patients, recently published final BASIL trial data confirm the superiority of open surgical bypass. 21 Moreover, some doctors have warned that bypass operation after failed angioplasty is not as successful as initial bypass operation.…”
Section: Discussionmentioning
confidence: 99%
“…20 Although there were several reports that suggested that this was advantageous for compromised patients, recently published final BASIL trial data confirm the superiority of open surgical bypass. 21 Moreover, some doctors have warned that bypass operation after failed angioplasty is not as successful as initial bypass operation.…”
Section: Discussionmentioning
confidence: 99%
“…ing autologous veins has and continues to be considered the most favorable treatment for CLI, endovascular techniques, including percutaneous transluminal angioplasty (PTA), have improved and now rival surgical bypass in terms of patient risk factors (11,30,31) (Fig. 2).…”
Section: Treatmentmentioning
confidence: 99%
“…This was the first study to support primary stent placement in the lower extremities. More recently, studies have also demonstrated that balloon PTA procedures can result in a 77%-100% technical success rate in BTK intervention (11). Furthermore, the recent introduction of long, low profile angioplasty balloon catheters and microwire systems have improved endovascular treatment approaches by extending the range of lesions that are treatable with a primary endovascular technique (11).…”
Section: Below-the-knee Disease-a Unique Subset Of CLImentioning
confidence: 99%
See 2 more Smart Citations